2020
DOI: 10.3389/fmicb.2020.02015
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Bluefin Tuna Mucosal Microbiome Is Influenced by Husbandry Method, Net Pen Location, and Anti-parasite Treatment

Abstract: Southern Bluefin Tuna Mucosal Microbiome had more similar microbial communities compared to other families. The finding that mucosal microbial communities are more similar in phylogenetically related fish species exposes an opportunity to develop mackerel as a model for tuna microbiome and parasite research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…Specifically, for scombrids, scarce information is available about gut microbiota composition. Alpha-diversity indexes values in the present study are in line with those described previously for other scombrids, such Spanish and king mackerel ( Scomberomorus maculatus and Scomberomorus cavalla , respectively) [ 65 ] and southern bluefin tuna [ 68 ]. Ley et al [ 69 ] described an inverse relation between gut microflora phylogenetic diversity and trophic level, being diversity higher in herbivorous than in carnivores’ organisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, for scombrids, scarce information is available about gut microbiota composition. Alpha-diversity indexes values in the present study are in line with those described previously for other scombrids, such Spanish and king mackerel ( Scomberomorus maculatus and Scomberomorus cavalla , respectively) [ 65 ] and southern bluefin tuna [ 68 ]. Ley et al [ 69 ] described an inverse relation between gut microflora phylogenetic diversity and trophic level, being diversity higher in herbivorous than in carnivores’ organisms.…”
Section: Discussionsupporting
confidence: 92%
“…This intra-specific variability in the bacterial relative abundance has been also described for other fish species such as the grey mullet ( Mugil cephalus ) [ 70 ] and codfishes [ 71 ]. Tenericutes has been also identified as the dominant gut community in the southern bluefin tuna and king mackerel, while Firmicutes in Spanish mackerel [ 65 , 68 ], suggesting that both phyla are part of the microbiota of scombrids. At genus level, gut microbial composition had higher proportion of Mycoplasma (Tenericutes Phylum), followed by Blautia and Dorea (Firmicutes phylum) and Bifidobacterium (Actinobacteria phylum).…”
Section: Discussionmentioning
confidence: 99%
“…3). These phyla typically dominate within the skin microbiome of fish species [14,29,[58][59][60]. Geographic and seasonal variations in the composition of the skin microflora have been recently reported in marine mammals, corals and fishes [10,12,61], suggesting that environmental conditions (biotic and abiotic) are strong determinants of the skin microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the consumption of tuna also poses a health risk, with the occasional development of histamine-producing bacteria (HPB) responsible for frequent fish poisoning cases [27,28]. Finally, despite the considerable nutritional value of this resource as well as the health hazard associated with its consumption, knowledge of the microbiome of tuna remains rudimentary [29].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbiota is important for the health and development of bluefin tuna, however, studies on this topic are limited [ 16 , 17 ]. Minich et al [ 17 ] investigated the microbial diversity associated with mucosal membranes, including the gut farmed southern bluefin tuna ( Thunnus maccoyii ) and showed that the microbiota structure was affected by pontoon location and treatment with an antihelminthic drug. Gatesoupe et al [ 16 ] investigated the change in intestinal microbiota in Atlantic bluefin tuna Thunnus thynnus larvae and showed that the microbiota varied greatly among individuals.…”
Section: Introductionmentioning
confidence: 99%